Social environment affects female preference for male body color during development in artificially selected varieties of Poecilia latipinna. Issue 5 (3rd September 2017) - MacLaren, R. David
Abstract : This study provides evidence for an effect of social environment on color morph preference during development in two artificially selected varieties of the live-bearing fish Poecilia latipinna . Black-colored females reared exclusively in the presence of white-colored adults preferred to associate with white vs black males when tested using a standard dichotomous choice design. Similarly, white females reared exclusively in the presence of black adults showed a preference for black males in identical dichotomous choice tests. However, both black and white females when reared separately in the presence of a mix of black and white adults showed no preference for either male color variety. A second round of testing revealed that their preferences (or lack thereof), although significantly weaker, persisted for at least a week after the initial tests during which the model groups were altered; groups reared in the presence of opposite-colored adults were exposed to mixed-color adults, while groups reared in the presence of mixed-color adults were exposed to opposite-color models. Taken together, these data indicate that the females' social environment during the first 2 months of life affected the development of preferences for male body color and further suggest such social learning could potentially influence mate and/or shoaling preferences for color and perhaps other traits in natural populations of P. latipinna .